Internalization of Values Four Corners In Educational Leadership towards Affirming the Pancasila Student Profile - Nurdin, Hisosiyan; Aqilah, Nur; B, Anatasia.; Alwi, Muhammad (Peneliti.net, 2024)
This study discusses